PERLINDUNGAN HUKUM BAGI KONSUMEN PEMBELI SATUAN RUMAH SUSUN TERHADAP STATUS KEPEMILIKAN SATUAN RUMAH SUSUN - Sujateruna, Randy; Puspawati, I Gusti Ayu; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2014)
Problems flats sticking on the surface due to the high investment flats that arenot coupled with knowledge of the law relating to flats, they do not pay attention tothose aspects that would later cause problems for consumers or residents of theapartment as well as the status of legal protection of ownership rights to land.Consumer the flats have legal protection with full probative force or it’s perfect overthe land title of an apartment and meet the requirements as written in the Law Number20 of 2011 on Flats. Goal in this case is to determine the legal protection for consumersagainst the ownership of apartment units and transition process to determine the rightsof consumers in the flats by Law Number 20 of 2011 on Flats. This research isnormative legal research. The final conclusion is by issuing the certificate of ownershipfor Flats, it guarantees the legal certainty and the rights certainty of the ownership offlats for the consumer and transitioning the ownership rights of the flat unit can bemade in PPAT deed and registered at the local land office.
Keywords: Legal Protection, Consumer, The ownership of Land Right, The Flats Unit